Anaerobic biotransformation of roxarsone regulated by sulfate: Degradation, arsenic accumulation and volatilization. (December 2020) - Tang, Rui; Wu, Guangxue; Yue, Zhengbo; Wang, Wei; Zhan, Xinmin; Hu, Zhen-Hu
Abstract: Roxarsone, an extensively used organoarsenical feed additive, is often pooled in livestock wastewater. Sulfate exists ubiquitously in livestock wastewater and is capable for arsenic remediation. However, little is known about impacts of sulfate on roxarsone biotransformation during anaerobic digestion of livestock wastewater. In this study, the biodegradation of 5.0 mg L −1 roxarsone, and the accumulation and volatilization of the generated arsenical metabolites in a sulfate-spiked upflow anaerobic granular blanket reactor were investigated. Based on the analysis of degradation products, the nitro and arsenate groups of roxarsone were successively reduced to amino and arsenite groups before the C–As bond cleavage. Effluent arsenic concentration was ∼0.75 mg L −1, of which 82.9–98.5% were organoarsenicals. The maximum arsenic volatilization rate reached 32.6 μg-As kg −1 -VS d −1 . Adding 5.0 mg L −1 sulfate enabled 66.7% and 45.9% decrease in inorganic arsenic concentration and arsenic volatilization rate, respectively. Arsenic content in the anaerobic granular sludge (AGS) was accumulated to 1250 mg kg −1 within 420 days. Based on the results of FESEM-EDS and XPS, sulfate addition induced arsenic precipitation in the AGS through the formation of orpiment. Arsenic in the effluent, biogas and AGS accounted for 52.9%, 0.01% and 47.1% of the influent arsenic when the reactor operated stably. The findings from this study suggest that sulfate has effectively regulatory effects on arsenic immobilization and volatilization during anaerobic digestion of organoarsenic-contaminated livestock wastewater. Graphical abstract: Image 1 Highlights: A degradation pathway of roxarsone into inorganic arsenic (As) was proposed. SO4 2− addition enabled a 66.7% decrease in inorganic As concentration. As content in the sludge increased from ∼5 to 1250 mg kg −1 within 420 days. SO4 2− addition triggered a 45.9% decrease in As volatilization rate. Most of influent As ended up in the effluent and sludge, with 0.01% volatilized.